Evaluating the impact of books in Chinese Studies: A case study of books authored by UCLA scholars - Xiong, Zequan; Duan, Yufeng (Malaysian Journal of Library and Information Science, 2019)
This study is the first comprehensive analysis to evaluate the impact of books in a particular field, namely, Chinese studies, authored by scholars at the University of California, Los Angeles (UCLA). Bibliometric and altmetric indicators were applied to evaluate the impact of books, and correlations between different indicators were analyzed using Spearman correlation coefficients. The results showed significant differences between impact ranks using both indicators. Bibliometric indicators, including citations, library holdings, and book reviews, mainly reflect the academic impact of books, while altmetric indicators, including Amazon sales and Goodreads ratings, mainly reflect the social impact of those books. The most influential books and scholars were obtained based on each of the two indicator types. This effort can benefit academic efforts to evaluate the impact of books using multiple indicators.